Behavioural health interventions in the Johns Hopkins Community Health Partnership: Integrated care as a component of health systems transformation. (December 2014) - Everett, Anita S.; Reese, Jennifer; Coughlin, Janelle; Finan, Patrick; Smith, Michael; Fingerhood, Michael; Berkowitz, Scott; Young, J. Hunter; Johnston, Diedre; Dunbar, Linda; Zollinger, Raymond; Ju, Jin; et al.
Abstract Health systems in the USA have received a mandate to improve quality while reining in costs. Several opportunities have been created to stimulate this transformation. This paper describes the design, early implementation and lessons learned for the behavioural components of the John Hopkins Community Health Partnership (J-CHiP) programme. J-CHiP is designed to improve health outcomes and reduce the total healthcare costs of a group of high healthcare use patients who are insured by the government-funded health insurance programmes, Medicaid and Medicare. These patients have a disproportionately high prevalence of depression, other psychiatric conditions, and unhealthy behaviours that could be addressed with behavioural interventions. The J-CHiP behavioural intervention is based on integrated care models, which include embedding mental health professionals into primary sites. A four-session behaviour-based protocol was developed to motivate self-efficacy through illness management skills. In addition to staff embedded in primary care, the programme design includes expedited access to specialist psychiatric services as well as a community outreach component that addresses stigma. The progress and challenges involved with developing this programme over a relatively short period of time are discussed.